Preparation process and structure of vehicle anti-riot front windshield
By using high-temperature reinforced special glass and multi-layer film structural design, combined with diaphragm preforming and high-pressure molding, the thickness and weight of automotive riot-proof glass is solved, and a thin and high-safe automotive front windshield is achieved.
Patent Information
- Application Number
- CN202411931463.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-08
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing automotive riot glass has a large thickness and heavier weight, making it difficult to bend the shaving piece, resulting in increased weight of the car, increased fuel consumption and insufficient safety performance.
Special glass with high temperature reinforcement treatment and combined with the multi-layer structure design of SGP film and TPU film, the diaphragm preforming process and high-pressure molding process are used to form a thin and light automotive front windshield with excellent riot resistance.
The light and thin design of the automotive riot-proof front windshield is realized, which reduces the weight of the car, reduces fuel consumption, and improves the impact resistance and safety of the glass, meeting the demand of the modern automobile industry for high safety performance.
Smart Images

Figure CN119773320A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of automobile accessories, in particular to a preparation process and structure of a riot-proof front windshield for a vehicle. Background Art
[0002] With the rapid development of the automobile industry, vehicle safety has become the focus of public attention. Especially when a vehicle is involved in an accident, the windshield is an important barrier to protect the safety of the passengers in the car, and its strength and impact resistance are crucial. Traditional car windshields are mainly made of ordinary glass or tempered glass. Although these materials have certain strength, they are easy to break into sharp fragments when subjected to strong impacts, such as car accidents or collisions with foreign objects, causing harm to the passengers.
[0003] In addition, although there are riot-proof glass products on the market, they are mainly used in special places such as jewelry display cabinets, garden villas, etc., but in the field of automotive glass, especially as front windshields, there is almost no application. The main reason is that traditional riot-proof glass has problems such as large thickness and heavy weight, which not only increases the weight and fuel consumption of the car, but also increases the difficulty of riot-proof glass technology because the front windshield generally has a large curved surface.
[0004] In view of the shortcomings of the prior art, the present invention provides a preparation process for a riot-proof front windshield for a vehicle, aiming to solve the problems of thick thickness, heavy weight, and difficulty in bending and assembling riot-proof glass in the prior art. The present invention adopts special glass that has been subjected to high-temperature strengthening treatment, and combines the multi-layer structure design of SGP film and TPU film to realize a riot-proof front windshield for a vehicle that is both light and thin and has excellent riot-proof performance. This process not only reduces the weight of the vehicle and reduces fuel consumption, but also improves the safety and durability of the front windshield, meeting the demand for high safety performance in the modern automobile industry. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a process for preparing a riot-proof front windshield for a vehicle and a structure thereof, which solves the problems in the background art that the riot-proof glass is thick, heavy, and difficult to bend and assemble.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: a preparation process and structure of a riot-proof front windshield for a vehicle, the steps of which are as follows: S01. Material screening: Select special glass that has been subjected to high temperature strengthening treatment as the basic material. Special glass has excellent impact resistance; S02. Structural optimization design: Design the film preforming tooling to adapt to the curvature of the special glass. The tooling is used to preform SGP film and TPU film; S03. Film preforming: Preform the SGP film and TPU film to make their shapes match the special glass; S04. Implementation of the gluing process: gluing the preformed diaphragm with the special glass to form a preliminary riot-proof structure; S05. Post-molding processing: pre-press and high-pressure process the glued glass and diaphragm combination to complete the molding of the riot-proof glass; S06. Finished product quality inspection: Inspect the size, curvature and explosion-proof grade of finished glass to ensure that the product meets relevant standards; S07. Product packaging and storage: Qualified anti-riot windshields shall be packaged and stored in a suitable environment to protect the product from damage.
[0007] Preferably, in the material screening in S01, a special glass that has been subjected to high temperature strengthening treatment is selected as the basic material. The thickness of the special glass is 5 mm to 8 mm, and the weight per square meter does not exceed 20 kg. The special glass should have an impact resistance at least 3 times that of ordinary glass, specifically, it can withstand an impact energy of not less than 3.5 joules without breaking.
[0008] Preferably, the structural optimization design in S02 includes designing a diaphragm preforming tooling to adapt to the curvature of the shape of the special glass, the tooling is used to preform SGP film and TPU film, wherein the thickness of the SGP film is 0.3mm to 0.7mm, and the thickness of the TPU film is 1.5mm to 2.5mm.
[0009] Preferably, the diaphragm preforming process in S03 includes preforming the SGP film and the TPU film to make their shapes match the special glass, and the preforming process is performed at a temperature of 120° C. to 180° C. for 30 to 60 minutes; the preforming process ensures that the preforming effect of the diaphragm meets the requirements of the gluing process to achieve seamless bonding between the diaphragm and the glass; Among them, the gluing process requires seamless bonding between the diaphragm and the special glass, ensuring that there is no glue overflow and no gaps in the glue seams, and that the bonding surfaces are in full contact to ensure the firmness and sealing of the structure; at the same time, the gluing process needs to be precisely controlled to meet specific optical performance standards, such as optical parallelism and center error, to ensure that the optical properties of the bonded parts meet the technical specifications.
[0010] Preferably, the gluing process in S04 includes gluing the preformed diaphragm to the special glass to form a preliminary anti-riot structure, and the gluing process uses a specific adhesive, which has the characteristic of rapid curing at room temperature, and the curing time does not exceed 2 hours; the gluing process ensures that the bonding strength between the diaphragm and the glass reaches or exceeds 5MPa to achieve structural stability and durability; Among them, the adhesive is an epoxy resin-based adhesive: the adhesive contains the following components, calculated in parts by weight: epoxy resin: 40-60 parts; epoxy diluent: 5-10 parts; curing agent: 30-50 parts; photobase generator: 0.1-2 parts; stabilizer: 0.1-2 parts; toughening agent: 5-10 parts; filler: 20-40 parts; additive: 0.2-2 parts.
[0011] Preferably, the post-molding treatment in S05 includes pre-pressing and high-pressure treatment of the bonded glass and diaphragm combination to complete the molding of the riot-proof glass. The high-pressure treatment is carried out under a pressure of 15 to 25 MPa for a duration of 1 to 3 hours. The high-pressure treatment ensures the structural stability of the riot-proof glass so that it can withstand strong external impacts.
[0012] Preferably, the finished product quality inspection in S06 includes inspection of the size, curvature and riot-proof grade of the finished glass to ensure that the product meets relevant standards, including but not limited to the total thickness and weight of the glass not exceeding 18KG per square meter, and reaching riot-proof protection grade B; the inspection includes testing the impact resistance of the glass to ensure that it can withstand at least 100 joules of impact energy.
[0013] Preferably, the product packaging and storage in S07 includes packaging qualified explosion-proof front windshields and storing them in a suitable environment to protect the products from damage. The environmental conditions are that the temperature is controlled at 15°C to 25°C and the humidity is controlled at 40% to 60%. The packaging materials should have good moisture-proof and shock-proof properties to ensure that the glass will not be damaged by external factors during transportation and storage.
[0014] Preferably, it includes SGP film, TPU film and special glass, the TPU film is provided with two layers, which are respectively glued to the inner and outer sides of the SGP film, the special glass is provided with two layers, and the SGP film and the TPU film are located between the two layers of special glass, and the outer surface of the TPU film is glued to the inner side of the special glass.
[0015] The present invention provides a process for preparing a riot-proof front windshield for a vehicle and its structure. It has the following beneficial effects: (1) Solving the problem of thick and heavy riot-proof glass: The present invention significantly reduces the weight of riot-proof glass by using thin and light special glass and optimized diaphragm structure design; the thickness of the special glass is controlled at 5 mm to 8 mm, and the weight per square meter does not exceed 20 kg, which effectively reduces the overall weight of the car, reduces fuel consumption, and improves fuel efficiency; this design maintains the strength and riot-proof performance of the glass at the same time, solving the problem of reduced vehicle performance due to the thickness and weight of traditional riot-proof glass; (2) Solving the problem of large curved surface of the front windshield and high process difficulty: The anti-riot front windshield for automobile of the present invention is designed through structural optimization, especially the application of film preforming tooling, so that the SGP film and TPU film can accurately match the curvature of the special glass; this preforming process is carried out at a temperature of 120°C to 180°C and lasts for 30 to 60 minutes, ensuring seamless bonding between the film and the glass, improving the process accuracy and yield rate, and solving the process difficulty problem caused by the large curved surface of the front windshield; (3) Improving the optical performance and safety of the windshield: The vehicle riot-proof windshield of the present invention takes the optimization of optical performance into consideration in its structural design. By precisely controlling the manufacturing process of the special glass, light distortion is reduced, ensuring that the driver has a clear field of vision under various lighting conditions. At the same time, by using a specific adhesive, the bonding strength between the diaphragm and the glass reaches or exceeds 5MPa, which greatly enhances the stability and durability of the structure and improves the safety of the windshield. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 It is a schematic diagram of the process of the present invention; Figure 2 It is a schematic diagram of the internal structure of the present invention; Figure 3 It is a front view structural schematic diagram of the present invention; Figure 4 It is a side view structural schematic diagram of the present invention.
[0017] In the figure, 1. SGP film; 2. TPU film; 3. Special glass. DETAILED DESCRIPTION
[0018] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1
[0019] S01. Material selection: Select special glass 3 that has been subjected to high temperature strengthening treatment, with a thickness of 6 mm and a weight of 18 kg per square meter. The impact resistance of the special glass 3 is at least 3 times that of ordinary glass, and can withstand an impact energy of no less than 3.5 joules without breaking.
[0020] S02. Structural optimization design: Design the film preforming tooling to adapt to the curvature of the special glass 3, the thickness of the SGP film 1 is 0.5mm, and the thickness of the TPU film 2 is 2mm. The tooling design takes into account the geometric shape of the glass and the required anti-riot performance, and optimizes the overall strength and safety of the anti-riot structure.
[0021] S03. Film preforming treatment: The SGP film 1 and the TPU film 2 are preformed at 150°C for 45 minutes. The preforming treatment ensures that the preforming effect of the film meets the requirements of the bonding process to achieve seamless bonding between the film and the glass.
[0022] S04. Implementation of bonding process: Use a specific epoxy resin-based adhesive to bond the SGP film 1 and the TPU film 2 to the special glass 3, and the curing time shall not exceed 2 hours. The adhesive contains the following components, in parts by weight: 50 parts of epoxy resin, 8 parts of epoxy diluent, 40 parts of curing agent, 1 part of photobase generator, 1 part of stabilizer, 8 parts of toughening agent, 30 parts of filler, and 1 part of auxiliary agent. The bonding process ensures that the bonding strength between the film and the glass reaches or exceeds 5MPa.
[0023] S05. Post-molding treatment: High pressure treatment is performed at a pressure of 20MPa for 2 hours. High pressure treatment ensures the structural stability of the riot glass, enabling it to withstand strong impacts from the outside.
[0024] S06. Finished product quality inspection: Inspect the size, curvature and anti-riot grade of the finished glass to ensure that the product meets the relevant standards, including but not limited to the total thickness and weight of the glass not exceeding 18KG per square meter, and reaching the anti-riot protection grade B.
[0025] S07. Product packaging and storage: Store in an environment with a temperature of 15℃ to 25℃ and a humidity of 40% to 60%, using moisture-proof and shock-proof packaging materials. The packaging materials have good moisture-proof and shock-proof properties to ensure that the glass will not be damaged by external factors during transportation and storage. Example 2
[0026] S01. Material selection: Select special glass 3 that has been subjected to high temperature strengthening treatment, with a thickness of 7 mm and a weight of 19 kg per square meter. The impact resistance of the special glass 3 is at least 3 times that of ordinary glass, and can withstand an impact energy of no less than 3.5 joules without breaking.
[0027] S02. Structural optimization design: Design the film preforming tooling to adapt to the curvature of the special glass 3, the thickness of the SGP film 1 is 0.4mm, and the thickness of the TPU film 2 is 1.8mm. The tooling design takes into account the geometric shape of the glass and the required anti-riot performance, and optimizes the overall strength and safety of the anti-riot structure.
[0028] S03. Film preforming treatment: The SGP film 1 and the TPU film 2 are preformed at 130°C for 50 minutes. The preforming treatment ensures that the preforming effect of the film meets the requirements of the bonding process to achieve seamless bonding between the film and the glass.
[0029] S04. Implementation of bonding process: Use a specific epoxy resin-based adhesive to bond the SGP film 1 and the TPU film 2 to the special glass 3, and the curing time shall not exceed 2 hours. The adhesive contains the following components, in parts by weight: 45 parts of epoxy resin, 7 parts of epoxy diluent, 35 parts of curing agent, 0.5 parts of photobase generator, 0.5 parts of stabilizer, 6 parts of toughening agent, 25 parts of filler, and 0.5 parts of auxiliary agent. The bonding process ensures that the bonding strength between the film and the glass reaches or exceeds 5MPa.
[0030] S05. Post-molding treatment: High pressure treatment is performed at a pressure of 18MPa for 1.5 hours. High pressure treatment ensures the structural stability of the riot-proof glass, enabling it to withstand strong impacts from the outside.
[0031] S06. Finished product quality inspection: Inspect the size, curvature and anti-riot grade of the finished glass to ensure that the product meets the relevant standards, including but not limited to the total thickness and weight of the glass not exceeding 19KG per square meter, and reaching the anti-riot protection grade B.
[0032] S07. Product packaging and storage: Store in an environment with a temperature of 15℃ to 25℃ and a humidity of 40% to 60%, using moisture-proof and shock-proof packaging materials. The packaging materials have good moisture-proof and shock-proof properties to ensure that the glass will not be damaged by external factors during transportation and storage. Example 3
[0033] S01. Material selection: Select special glass 3 that has been subjected to high temperature strengthening treatment, with a thickness of 5.5 mm and a weight of 17 kg per square meter. The impact resistance of the special glass 3 is at least three times that of ordinary glass, and can withstand an impact energy of no less than 3.5 joules without breaking.
[0034] S02. Structural optimization design: Design the film preforming tooling to adapt to the curvature of the special glass 3, the thickness of the SGP film 1 is 0.6mm, and the thickness of the TPU film 2 is 2.2mm. The tooling design takes into account the geometric shape of the glass and the required anti-riot performance, and optimizes the overall strength and safety of the anti-riot structure.
[0035] S03. Film preforming treatment: The SGP film 1 and the TPU film 2 are preformed at 160°C for 40 minutes. The preforming treatment ensures that the preforming effect of the film meets the requirements of the bonding process to achieve seamless bonding between the film and the glass.
[0036] S04. Implementation of bonding process: Use a specific epoxy resin-based adhesive to bond the SGP film 1 and the TPU film 2 to the special glass 3, and the curing time shall not exceed 2 hours. The adhesive contains the following components, in parts by weight: 55 parts of epoxy resin, 9 parts of epoxy diluent, 45 parts of curing agent, 1.5 parts of photobase generator, 1.5 parts of stabilizer, 9 parts of toughening agent, 35 parts of filler, and 1.5 parts of additive. The bonding process ensures that the bonding strength between the film and the glass reaches or exceeds 5MPa.
[0037] S05. Post-molding treatment: High pressure treatment is performed at a pressure of 22MPa for 2.5 hours. High pressure treatment ensures the structural stability of the riot glass, enabling it to withstand strong impacts from the outside.
[0038] S06. Finished product quality inspection: Inspect the size, curvature and anti-riot grade of the finished glass to ensure that the product meets the relevant standards, including but not limited to the total thickness and weight of the glass not exceeding 17KG per square meter, and reaching the anti-riot protection grade B.
[0039] S07. Product packaging and storage: Store in an environment with a temperature of 15℃ to 25℃ and a humidity of 40% to 60%, using moisture-proof and shock-proof packaging materials. The packaging materials have good moisture-proof and shock-proof properties to ensure that the glass will not be damaged by external factors during transportation and storage.
[0040] Comparative Example 1: S01. Material screening: Ordinary glass is selected as the base material, with a thickness of 8mm and a weight of 25kg per square meter. This ordinary glass has not been subjected to high temperature strengthening treatment, and its impact resistance does not meet the standards of special glass.
[0041] S02. Structural optimization design: No membrane preforming tooling is used, ordinary glass is directly used for processing, and SGP membrane 1 and TPU membrane 2 are not used.
[0042] S03. Film preforming treatment: Since SGP film 1 and TPU film 2 were not used, no preforming treatment was performed.
[0043] S04. Implementation of bonding process: No specific epoxy resin-based adhesive was used, but conventional adhesives were used to bond glass to other materials, which takes a long time to cure.
[0044] S05. Post-molding processing: No pre-pressing or high-pressure treatment is performed, and the glass is formed only through basic cutting and grinding.
[0045] S06. Finished product quality inspection: basic size and curvature inspection was carried out, but no impact resistance and riot grade testing was performed.
[0046] S07. Product packaging and storage: Storage in ordinary environments without the use of moisture-proof and shock-proof packaging materials may cause damage to the glass during transportation and storage.
[0047] Comparative Example 2: S01. Material selection: Select special glass 3 with a thickness of 10 mm and a weight of 22 kg per square meter. Although special glass is used, its thickness and weight are higher than the special glass in the embodiment.
[0048] S02. Structural optimization design: A diaphragm preforming tooling was designed, the thickness of the SGP film 1 was 0.2 mm, and the thickness of the TPU film 2 was 1.2 mm, which were different from the diaphragm thickness used in the embodiment.
[0049] S03. Diaphragm preforming treatment: The preforming treatment is performed at 100° C. for 30 minutes. The treatment conditions are different from those in the embodiment.
[0050] S04. Implementation of the gluing process: Using a conventional adhesive, which has a long curing time and insufficient bonding strength, is different from the fast-curing epoxy resin-based adhesive used in the embodiment.
[0051] S05. Post-molding treatment: high pressure treatment is performed at a pressure of 10 MPa for 1 hour, and the pressure and duration are lower than those in the embodiment.
[0052] S06. Finished product quality inspection: Dimension and curvature inspections were performed, but no impact resistance and riot grade tests were performed.
[0053] S07. Product packaging and storage: Storage in ordinary environments without the use of moisture-proof and shock-proof packaging materials may cause damage to the glass during transportation and storage.
[0054] In order to compare the performance differences between the embodiments of the present invention and the comparative examples in detail, a series of tests were conducted and organized into the following three tables to show the specific data comparison results: Table 1: Comparison of material performance data Experiment number Material Type Thickness(mm) Weight(kg / m²) Impact resistance (joule) Flexural strength(MPa) Example 1 Special glass 6 18 ≥3.5 180 Example 2 Special glass 7 19 ≥3.5 190 Example 3 Special glass 5.5 17 ≥3.5 170 Comparative Example 1 Ordinary glass 8 25 <1.5 70 Comparative Example 2 Special glass 10 22 ≥3.5 160 The special glass 3 used in Examples 1, 2, and 3 is superior to ordinary glass in terms of impact resistance, showing an impact strength at least three times that of ordinary glass while maintaining a relatively light weight. The ordinary glass in Example 1 has poor impact resistance and is heavy, which is not conducive to improving vehicle performance. Although special glass is also used in Example 2, its thickness and weight are both higher than those of the examples.
[0055] Table 2: Comparison of post-processing data between gluing and molding Experiment number SGP film thickness (mm) TPU film thickness (mm) Preforming temperature(℃) Preforming time (min) Adhesive curing time (hr) Bonding strength (MPa) High pressure treatment pressure (MPa) High pressure treatment time (hr) Example 1 0.5 2 150 45 0.33 ≥5 20 2 Example 2 0.4 1.8 130 50 0.33 ≥5 18 1.5 Example 3 0.6 2.2 160 40 0.33 ≥5 22 2.5 Comparative Example 1 - - - - - - - - Comparative Example 2 0.2 1.2 100 30 >2 <3 10 1 Table 3: Comparison of finished product quality inspection and storage conditions data Experiment number Total thickness(mm) Weight(kg / m²) Riot level Optical parallelism error (mm) Storage temperature(℃) Storage humidity(%) Packaging material characteristics Example 1 8.88 18 Class B 0.5 15-25 40-60 Moisture-proof and shock-proof Example 2 8.5 19 Class B 0.5 15-25 40-60 Moisture-proof and shock-proof Example 3 9 17 Class B 0.5 15-25 40-60 Moisture-proof and shock-proof Comparative Example 1 - 25 - - Uncontrolled Uncontrolled none Comparative Example 2 10.5 22 - - Uncontrolled Uncontrolled none Combined with Tables 2-3, it can be seen that the SGP film and TPU film and epoxy resin-based adhesive used in Examples 1, 2, and 3 all achieve rapid curing and high bonding strength, which is crucial for improving the structural stability and durability of the front windshield.
[0056] The high pressure treatment pressure and time in Examples 1, 2, and 3 are higher than those in Comparative Example 2, which helps to further enhance the anti-riot performance of the finished product. Comparative Example 1 does not use special adhesives and high pressure treatment, which may lead to insufficient bonding strength and poor structural stability. The adhesive in Comparative Example 2 has a long curing time and insufficient bonding strength, which may affect the long-term performance and safety of the front windshield; the finished products of Examples 1, 2, and 3 all reach anti-riot grade B, and the optical parallelism error is controlled within 0.5 mm, ensuring good optical performance.
[0057] Examples 1, 2, and 3 are all stored in a strictly controlled environment and use moisture-proof and shock-proof packaging materials, which helps to protect the finished product from damage during transportation and storage and extend the product life. Comparative Example 1 lacks suitable storage conditions and packaging materials, which may cause the finished product to be damaged during storage, affecting product performance and service life.
[0058] In summary, the embodiments are superior to the comparative examples in terms of material selection, gluing process, post-molding processing, and storage conditions of finished products, and show better performance and safety.
[0059] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is defined by the attached claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention. Any figure mark in the claims should not be regarded as limiting the claims involved.
[0060] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A process for preparing a riot-proof front windshield for a vehicle, characterized in that: The steps are as follows: S01. Material screening: selecting a special glass (3) that has been subjected to high temperature strengthening treatment as a base material, wherein the special glass (3) has excellent impact resistance; S02. Structural optimization design: designing a film preforming tool to adapt to the curvature of the special glass (3), the tool being used to preform the SGP film (1) and the TPU film (2); S03. Preforming of the film: Preforming the SGP film (1) and the TPU film (2) to make their shapes match those of the special glass (3); S04. Implementation of the gluing process: gluing the preformed membrane to the special glass (3) to form a preliminary riot-proof structure; S05. Post-molding processing: pre-press and high-pressure process the glued glass and diaphragm combination to complete the molding of the riot-proof glass; S06. Finished product quality inspection: Inspect the size, curvature and explosion-proof grade of finished glass to ensure that the product meets relevant standards; S07. Product packaging and storage: Qualified anti-riot windshields shall be packaged and stored in a suitable environment to protect the product from damage.
2. A process for preparing a riot-proof front windshield for a vehicle according to claim 1, characterized in that: The material screening in S01 selects a special glass (3) that has been subjected to high temperature strengthening treatment as a basic material. The thickness of the special glass (3) is 5 mm to 8 mm, and the weight per square meter does not exceed 20 kg. The special glass (3) should have an impact resistance at least three times that of ordinary glass, specifically, it can withstand an impact energy of not less than 3.5 joules without breaking.
3. The process for preparing a riot-proof front windshield for a vehicle according to claim 1, characterized in that: The structural optimization design in S02 includes designing a film preforming tool to adapt to the curvature of the shape of the special glass (3), wherein the tool is used to preform the SGP film (1) and the TPU film (2), wherein the thickness of the SGP film (1) is 0.3 mm to 0.7 mm, and the thickness of the TPU film (2) is 1.5 mm to 2.5 mm.
4. The process for preparing a riot-proof front windshield for a vehicle according to claim 1, characterized in that: The diaphragm preforming process in S03 includes preforming the SGP film (1) and the TPU film (2) so that their shapes match the special glass (3), the preforming process being performed at a temperature of 120° C. to 180° C. for a duration of 30 to 60 minutes; the preforming process ensures that the preforming effect of the diaphragm meets the requirements of the bonding process, so as to achieve seamless bonding between the diaphragm and the glass; The gluing process requires that the film and the special glass (3) be seamlessly bonded to ensure that there is no glue overflow and no gaps in the glue seam, and that the bonding surfaces are in full contact to ensure the firmness and sealing of the structure. At the same time, the gluing process needs to be precisely controlled to meet specific optical performance standards, such as optical parallelism and center error, to ensure that the optical properties of the bonded parts meet the technical specifications.
5. The process for preparing a riot-proof front windshield for a vehicle according to claim 1, characterized in that: The bonding process in S04 includes bonding the preformed film to the special glass (3) to form a preliminary protective structure. The bonding process uses a specific adhesive that has a fast curing property at room temperature and a curing time of no more than 2 hours. The bonding process ensures that the bonding strength between the film and the glass reaches or exceeds 5 MPa to achieve structural stability and durability. Among them, the adhesive is an epoxy resin-based adhesive: the adhesive contains the following components, calculated in parts by weight: epoxy resin: 40-60 parts; epoxy diluent: 5-10 parts; curing agent: 30-50 parts; photobase generator: 0.1-2 parts; stabilizer: 0.1-2 parts; toughening agent: 5-10 parts; filler: 20-40 parts; additive: 0.2-2 parts.
6. The process for preparing a riot-proof front windshield for a vehicle according to claim 1, characterized in that: The post-molding treatment in S05 includes pre-pressing and high-pressure treatment of the bonded glass and diaphragm combination to complete the molding of the riot-proof glass. The high-pressure treatment is carried out under a pressure of 15 to 25 MPa and lasts for 1 to 3 hours. The high-pressure treatment ensures the structural stability of the riot-proof glass so that it can withstand strong external impacts.
7. The process for preparing a riot-proof front windshield for a vehicle according to claim 1, characterized in that: The finished product quality inspection in S06 includes the inspection of the size, curvature and anti-riot level of the finished glass to ensure that the product meets the relevant standards, including but not limited to the total thickness and weight of the glass not exceeding 18KG per square meter, and reaching the anti-riot protection level B; the inspection includes testing the impact resistance of the glass to ensure that it can withstand at least 100 joules of impact energy.
8. The process for preparing a riot-proof front windshield for a vehicle according to claim 1, characterized in that: The product packaging and storage in S07 includes packaging qualified anti-riot windshields and storing them in a suitable environment to protect the products from damage. The environmental conditions are that the temperature is controlled at 15°C to 25°C and the humidity is controlled at 40% to 60%. The packaging materials should have good moisture-proof and shock-proof properties to ensure that the glass will not be damaged by external factors during transportation and storage.
9. A riot-proof front windshield structure for a vehicle according to any one of claims 1 to 8, characterized in that: The invention comprises an SGP film (1), a TPU film (2) and special glass (3), wherein the TPU film (2) is provided with two layers, which are respectively glued to the inner and outer sides of the SGP film (1); the special glass (3) is provided with two layers, and the SGP film (1) and the TPU film (2) are located between the two layers of special glass (3); and the outer surface of the TPU film (2) is glued to the inner side of the special glass (3).
Citation Information
Patent Citations
Coloured glass lens for eyeglasses and method for making it
CN104520757A
Epoxy glue binder for encapsulating of flexible screen
CN110684493A
Impact-resistant film and laminated glass having same
CN111421916A
Production method of SGP laminated glass
CN111823670A
SGP laminated glass and processing technology thereof
CN112109418A